2014
DOI: 10.1111/1744-7917.12072
|View full text |Cite
|
Sign up to set email alerts
|

Response of Solanum tuberosum to Myzus persicae infestation at different stages of foliage maturity

Abstract: Young leaves of the potato Solanum tuberosum L. cultivar Kardal contain resistance factors to the green peach aphid Myzus persicae (Sulzer) (Hemiptera: Aphididae) and normal probing behavior is impeded. However, M. persicae can survive and reproduce on mature and senescent leaves of the cv. Kardal plant without problems. We compared the settling of M. persicae on young and old leaves and analyzed the impact of aphids settling on the plant in terms of gene expression. Settling, as measured by aphid numbers stay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Differences in resistance levels between young and old leaves have been observed in potato (Solanum tuberosum) against aphids. Probing of the green peach aphid Myzus persicae on young leaves was impeded, whereas no obstacles were found on mature and senescent leaves (Alvarez et al 2014).…”
Section: Introductionmentioning
confidence: 87%
“…Differences in resistance levels between young and old leaves have been observed in potato (Solanum tuberosum) against aphids. Probing of the green peach aphid Myzus persicae on young leaves was impeded, whereas no obstacles were found on mature and senescent leaves (Alvarez et al 2014).…”
Section: Introductionmentioning
confidence: 87%
“…An explanation for this is that B. aphidicola plays a role in stylet penetration in the plant tissues, presumably through an influence in salivation or the production of specific proteins, such as GroEL, that act as effectors in the aphid's host plant. It is known that M. persicae probing on S. tuberosum , S. stoloniferum , and A. thaliana plants promote the expression of genes related to changes in the physiological state of the plant (Thompson & Goggin, ; De Vos et al ., ; Goggin, ; Alvarez et al ., , ). This changes represent a manipulation of the plant physiology for the aphids own benefit, (Zhu‐Salzman et al ., ; Alvarez et al ., ) and B. aphidicola may be involved in this.…”
Section: Discussionmentioning
confidence: 99%
“…Plant responses to aphids are very complex; in Arabidopsis thaliana a large number of general metabolism genes change their expression influencing changes in the physiological state of the plants, which is proposed to be a manipulation of the plant physiology for the aphids own benefit (De Vos et al ., , ; Thompson & Goggin, ; Goggin, ). Furthermore, the transcriptomes of S. tuberosum and S. stoloniferum plants infested by M. persicae show changes in the expression of a large number of pathogenesis related genes (PR genes) and genes related to signal transduction dependent on salicylic acid (SA) (Alvarez et al ., ; Alvarez et al ., ). The manipulation of plant physiology performed by aphids is proposed to be a condition for plant acceptance (Zhu‐Salzman et al ., ; Alvarez et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar observation was made in Senecio, in which Leiss et al (2009) found a significant positive correlation between leaf age and silvering damage in a choice assay, suggesting a higher thrips resistance in younger leaves. Another example of higher insect resistance in younger leaves is described by Alvarez et al (2014), who found that green peach aphid Myzus persicae (Sulzer) resistance in younger leaves of potato was higher than in older leaves. In contrast, the susceptible pepper accession CGN17219 shows a higher larval development on younger leaves compared to older leaves.…”
Section: Leaf Age Affects Thrips Resistancementioning
confidence: 97%